Chasing the Yellow Demon. Issue 1 (30th January 2017) - Johnson, Ian
Abstract : Author's note: A few years ago, I read David Johnson's Spectacle and Sacrifice: The Ritual Foundations of Village Life in North China . 1 The book immediately caught my attention because it dealt with parts of China that I know well: southern Hebei and eastern Shanxi provinces, where I was conducting research for a new book. Johnson describes festivals that helped bind together communities, and in several cases had information showing that some of them had been revived after the Cultural Revolution. One, particularly, seemed noteworthy: Guyi Village in the south of Hebei Province. This is near the steel-making city of Handan and one of the most polluted parts of China. I had been there several times and was fascinated with the idea that this area could also be home to elaborate, multi-day rituals that seemed otherwise not to exist in North China. According to Johnson's informants, local scholars had visited the village in the 1990s and seen exciting performances of Zhuo Huanggui, or Chasing the Yellow Demon, an exorcistic purging ritual performed at the end of the fifteen-day Chinese New Year's festival. I contacted local officials and academics, who were unsure if the ritual would be performed again. No one, it seemed, had been out to the village in years. So in mid-February 2014, I set off to see if anything was left of these complex performances. 2